2008
DOI: 10.1152/ajpregu.90367.2008
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of fat metabolism in skeletal muscle of normal-weight, overweight, and obese humans

Abstract: Velan SS, Said N, Durst C, Frisbee S, Frisbee J, Raylman RR, Thomas MA, Rajendran VM, Spencer RG, Alway SE. Distinct patterns of fat metabolism in skeletal muscle of normal-weight, overweight, and obese humans. Am J Physiol Regul Integr Comp Physiol 295: R1060 -R1065, 2008. First published July 30, 2008 doi:10.1152/ajpregu.90367.2008The link between body weight, lipid metabolism, and health risks is poorly understood and difficult to study. Magnetic resonance spectroscopy (MRS) permits noninvasive investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 44 publications
(68 reference statements)
4
49
1
Order By: Relevance
“…7), obtained from the location where the MRS was performed, showed the fibers to be predominantly parallel to the magnetic field direction. The ϪCH 3 signal from total creatine (phosphocreatine and creatine) showed a triplet centered at 3.03 ppm with the splitting being due to residual dipolar coupling; this outcome has been observed from skeletal muscle that is variously orientated relative to the direction of the magnetic field (4,5,31,(42)(43)(44). This independently confirmed that the fibers were predominantly parallel to the magnetic field.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…7), obtained from the location where the MRS was performed, showed the fibers to be predominantly parallel to the magnetic field direction. The ϪCH 3 signal from total creatine (phosphocreatine and creatine) showed a triplet centered at 3.03 ppm with the splitting being due to residual dipolar coupling; this outcome has been observed from skeletal muscle that is variously orientated relative to the direction of the magnetic field (4,5,31,(42)(43)(44). This independently confirmed that the fibers were predominantly parallel to the magnetic field.…”
Section: Discussionsupporting
confidence: 52%
“…Specifically, the detection of two lipid pools in skeletal muscle with a 1 H NMR spectroscopic chemical shift difference between peaks of 0.2 parts per million (ppm) is attributed to the intra-and extramyocellular lipid (IMCL and EMCL, respectively) pools. Several groups have now established the fact that the IMCL is strongly associated with insulin resistance and diabetes in both rodents and humans (5,15,31,42,44). Recently, the presence of two lipid pools, including IMCL and EMCL, was demonstrated in cardiac muscle of patients with muscular dystrophy (34).…”
mentioning
confidence: 99%
“…LIPID MEASUREMENTS by proton magnetic resonance spectroscopy (MRS) have been useful in understanding a number of disorders, including diabetes (1-3), obesity (3)(4)(5), liver disease (6,7), and cancer (3,(8)(9)(10). It has been suggested that there may be a link between the composition of fatty tissue and the risk of suffering from such diseases (11,12).…”
mentioning
confidence: 99%
“…A defect in accumulating unsaturated fats might be supported by a defi cit in gene expression of specifi c transporters such as CD 36 ( 38 ). It should be noted that a decrease in unsaturation with the increase of the body mass index has been also found in skeletal human muscle ( 8 ). Such a decrease was interpreted focusing on the desaturase enzymes, termed ⌬ 9 , ⌬ 6 , ⌬ 5 , and ⌬ 4 , and positing increased activity of the fi rst two and decreased activity of ⌬ 5 ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…areas of different peaks in NMR spectra ( 8,23,24 ). Strobel et al ( 23 ) have demonstrated that reliable calculation of peak areas requires fi tting of spectral lines and correction of peak intensity by the T2 value.…”
Section: Discussionmentioning
confidence: 99%